2019
DOI: 10.1101/581827
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A stable pollination environment limits current but not potential evolution of floral traits

Abstract:  Plant´s exquisite variation in floral traits at a macroevolutionary level is often interpreted as the result of adaptations to pollinators. However, field studies measuring pollinator-mediated evolution of flowers often find little evidence for strong selection. A possible explanation is the prevalence of periods of stasis, when selection on flowers is relaxed under stable pollination conditions, followed by unstable periods where pollinator changes provide innovative selection.Here we asked if periods of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…; reviewed in Parachnowitsch et al, 2019) and are thus likely to require long-term consistent selection for a detectable response. This is in contrast to linear morphological traits that often present high values of heritability, even when measured in field conditions (Ashman & Majetic, 2006;Castellanos et al, 2019), and that have been shown to change in response to single mutations with implications for pollinator visitation (see Ding et al, 2017 for an example in Mimulus). For D. purpurea we are in the process of measuring heritability both in the field (using molecular markers) and in a common garden, and preliminary results from the field studies point towards very high and significant narrow sense heritabilities (h 2 > 0.45) for linear corolla traits (Castellanos M.C., unpubl.).…”
Section: Discussionmentioning
confidence: 85%
“…; reviewed in Parachnowitsch et al, 2019) and are thus likely to require long-term consistent selection for a detectable response. This is in contrast to linear morphological traits that often present high values of heritability, even when measured in field conditions (Ashman & Majetic, 2006;Castellanos et al, 2019), and that have been shown to change in response to single mutations with implications for pollinator visitation (see Ding et al, 2017 for an example in Mimulus). For D. purpurea we are in the process of measuring heritability both in the field (using molecular markers) and in a common garden, and preliminary results from the field studies point towards very high and significant narrow sense heritabilities (h 2 > 0.45) for linear corolla traits (Castellanos M.C., unpubl.).…”
Section: Discussionmentioning
confidence: 85%
“…In a study that compared floral traits across time from a site with known pollinator declines, contemporary populations had larger floral displays and longer receptivity compared to their ancestor population ( Thomann et al, 2015 ). Similarly, Castellanos et al (2019) demonstrate that stable pollinator environments can stifle current evolutionary change while maintaining heritable variation necessary for future adaptation.…”
Section: Land Use Change Affects Floral Traits Mediated By Pollinatomentioning
confidence: 97%
“…Datasets and R code for all analyses are available in the Dryad Digital Repository [ 74 ]. Supplementary methods, figures and tables are provided in the electronic supplementary material [ 75 ]. Raw sequence data can be accessed from the NCBI Sequence Read Archive (SRA) with BioProject accession PRJNA951080.…”
Section: Data Accessibilitymentioning
confidence: 99%